1989
DOI: 10.1523/jneurosci.09-11-03998.1989
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine and learning-induced plasticity in infant rat olfactory system

Abstract: Postnatal olfactory learning produces both a conditioned behavioral response and a modified olfactory bulb neural response to the learned odor. The present report describes the role of norepinephrine (NE) on both of these learned responses in neonatal rat pups. Pups received olfactory classical conditioning training from postnatal days (PN) 1-18. Training consisted of 18 trials with an intertrial interval of 24 hr. For the experimental group, a trial consisted of a pairing of unconditioned stimulus (UCS, strok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
196
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(209 citation statements)
references
References 78 publications
13
196
0
Order By: Relevance
“…The pups in the present experiment were subjected to training procedures but were not tested for recall because we wished to examine the role of pCREB specifically in the acquisition of olfactory learning. In previous studies, we (McLean et al 1993(McLean et al , 1996Langdon et al 1997;Price et al 1998), as well as others Leon 1986a, 1987;Sullivan et al 1989aSullivan et al , 1991, have shown that pups subjected to the different training procedures show predictable behavioral outcomes.…”
Section: Conditioning Experiments and Sacrificementioning
confidence: 51%
See 2 more Smart Citations
“…The pups in the present experiment were subjected to training procedures but were not tested for recall because we wished to examine the role of pCREB specifically in the acquisition of olfactory learning. In previous studies, we (McLean et al 1993(McLean et al , 1996Langdon et al 1997;Price et al 1998), as well as others Leon 1986a, 1987;Sullivan et al 1989aSullivan et al , 1991, have shown that pups subjected to the different training procedures show predictable behavioral outcomes.…”
Section: Conditioning Experiments and Sacrificementioning
confidence: 51%
“…While the selectivity of the pCREB increase for the pairing condition supports a special role of the CREB promoter in associative learning, future investigations should compare forward (Odor + Stroking) and backward (Stroking followed by Odor, nonlearning) pairing. A demonstration of an effect of pairing order, which is known to affect memory formation in this paradigm (McLean et al 1996;Sullivan and Hall 1988;Sullivan et al 1991;Sullivan et al 1989b;Wilson and Sullivan 1991), would provide the strongest test of the claim for a unique association between pCREB increases and associative memory formation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…LC activation paired with sensory input does produce longterm memory in some paradigms (Sullivan et al, 1989). In rat pup olfactory preference learning, ␤-adrenoceptor stimulation in the olfactory bulb paired with glutamatergic input from olfactory neurons produces an odor preference 24 hr later (Sullivan et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced release of noradrenaline (NA) within the MOB plays an important role in long-term synaptic plasticity and odor learning in a variety of contexts. These include olfactory conditioning in neonatal rats (Sullivan et al 1989(Sullivan et al , 1992(Sullivan et al , 2000Harley et al 2006;Zhang et al 2010;Shakhawat et al 2012), the learning of newborn lamb odors after parturition in sheep (Pissonnier et al 1985), odor discrimination after memory formation in mice (Doucette et al 2007;Shea et al 2008;Moreno et al 2012), a specific long-term suppression of mitral cell (MC) responses to paired odors in mice (Shea et al 2008), a long-term reduction of paired-pulse inhibition in neonatal rats (Wilson and Leon 1988), long-term enhancement of synchronized γ frequency oscillations in rat MOB slices (Gire and Schoppa 2008;Pandipati et al 2010), long-term potentiation (LTP) of synaptic strength in rat MOB slices (Yuan 2009;Zhang et al 2010), and a long-term suppression of presynaptic input to MCs in mice (Eckmeier and Shea 2014).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%